Immunogenicity and safety of a tetravalent E. coli O-antigen bioconjugate vaccine in animal models. Issue 35 (29th July 2016) - van den Dobbelsteen, Germie P.J.M.; Faé, Kellen C.; Serroyen, Jan; van den Nieuwenhof, Ingrid M.; Braun, Martin; Haeuptle, Micha A.; Sirena, Dominique; Schneider, Joerg; Alaimo, Cristina; Lipowsky, Gerd; Gambillara-Fonck, Veronica; Wacker, Michael; et al.
Highlights: An ExPEC vaccine (O1, O2, O6, O25) was made using a novel bioconjugation process. The 4-valent bioconjugated ExPEC vaccine was immunogenic in 3 animal models. Antibody persistence and boostability were demonstrated in rats. ExPEC-4V at full human dose was at the no observed adverse effect level in rats. Abstract: Background: Extra-intestinal pathogenic Escherichia coli (ExPEC) are major human pathogens; however, no protective vaccine is currently available. We assessed in animal models the immunogenicity and safety of a 4-valent E. coli conjugate vaccine (ExPEC-4V, serotypes O1, O2, O6 and O25 conjugated to Exotoxin A from Pseudomonas aeruginosa (EPA)) produced using a novel in vivo bioconjugation method. Methods: Three doses of ExPEC-4V (with or without aluminum hydroxide) were administered to rabbits (2 μg or 20 μg per O-antigen, subcutaneously), mice (0.2 μg or 2 μg per O-antigen, subcutaneously) and rats (0.4 μg or 4 μg per O-antigen, intramuscularly). Antibody persistence and boostability were evaluated in rats using O6-EPA monovalent conjugate (0.4 μg O-antigen/dose, intramuscularly). Toxicity was assessed in rats (16 μg total polysaccharide, intramuscularly). Serum IgG and IgM antibodies were measured by ELISA. Results: Robust antigen-specific IgG responses were observed in all animal models, with increased responses in rabbits when administered with adjuvant. O antigen-specific antibody responses persisted up to 168 days post-priming. Booster immunization induced a rapid recall response. Toxicity of ExPEC-4V when administered to rats was considered to be at the no observed adverse effect level. Conclusions: ExPEC-4V conjugate vaccine showed good immunogenicity and tolerability in animal models supporting progression to clinical evaluation.